2020
DOI: 10.1364/oe.382254
|View full text |Cite
|
Sign up to set email alerts
|

Transparency and tunable slow-fast light in a hybrid cavity optomechanical system

Abstract: We theoretically investigate the optomechanically induced transparency (OMIT) phenomenon in a hybrid optomechanical system composing of an optomechanical cavity and a traditional one. A Kerr medium is inserted in the optomechanical cavity and the other traps the atomic ensemble. We demonstrate the appearance of electromagnetically and optomechanically induced transparency when there is only Kerr medium or atoms in the system. We give an explicit explanation for the mechanism of the transparency. Moreover, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 86 publications
0
26
0
Order By: Relevance
“…Similarly to the radiation-pressure induced optical spring effect, the positive photothermal stiffness experienced during self-locking by the system is paralleled by a negative damping coefficient [34,35]. The amount by which the natural damping of the acoustic mode is modified by the photothermal interaction can be estimated by the eigenvalues of the Jacobian matrix [30,[55][56][57][58].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the radiation-pressure induced optical spring effect, the positive photothermal stiffness experienced during self-locking by the system is paralleled by a negative damping coefficient [34,35]. The amount by which the natural damping of the acoustic mode is modified by the photothermal interaction can be estimated by the eigenvalues of the Jacobian matrix [30,[55][56][57][58].…”
Section: Resultsmentioning
confidence: 99%
“…[195] Cross-Kerr effects have been investigated in parity-time-symmetric resonators, where there emerges the absorption-to-amplification switching by tuning the tunnel coupling. [196] In addition, these years have seen the introduction of other intriguing phenomena relevant to OMIT, such as nonlinear effects, [195,[197][198][199][200] Casimir force, [201] and loss-induced transparency (LIT). [202] As an induced transparency in optomechanical cavities, OMIT poses a new perspective of light storage and can be applied to inaccessible wavelength regions in EIT.…”
Section: Optomechanically Induced Transparencymentioning
confidence: 99%
“…In addition, these years have seen the introduction of other intriguing phenomena relevant to OMIT, such as nonlinear effects, [ 195,197–200 ] Casimir force, [ 201 ] and loss‐induced transparency (LIT). [ 202 ]…”
Section: Optomechanically Induced Transparencymentioning
confidence: 99%
“…Khan et al [58] recently reported controllable OMIT in a two-cavity optomechanical system due to the interference between the two possible routs for excitations. Liao et al [59] investigated OMIT in a hybrid optomechanical system with Kerr medium which could be tuned from slow light to fast light. In addition, Huang et al [63] studied the Fano resonance in a quadratic coupling optomechanical system with a nonlinear Kerr medium.…”
Section: Introductionmentioning
confidence: 99%